PENGEMBANGAN MODUL PPKN MENGGUNAKAN MODEL EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA - Sari Jusnita Br Ginting (EJoES (Educational Journal of Elementary School), 2021)
This study aims to produce PPKn modules on environmental love by using the example non example learning model to improve student learning activities. The results showed that the feasibility assessment by material experts obtained an average of 91.6%, the feasibility assessment by linguists obtained an average of 92.1%, the feasibility assessment by design experts obtained an average of 80%. Individual trials with an average of 80.5% in the good category, small group trials with an average of 85.4% in the excellent category, and limited field trials with an average of 88.4% in the very good category. The results of observations of student activities observed an average of 92.4%, The results of observations of student activities asked an average of 85.6%, The results of observations of student activities tried with an average of 84.9%, The results of observations of student activities associated with reasoning an average of 89.4%, the results of observations of student activities communicate with an average of 83.9%. So the conclusion is that the PPKn module on environmental love using the example non example learning model is declared effective in generating student learning activities and outcomes. This is evidenced from the student learning achievement test. At the time of the pretest, the average value of the students was 69.8 and after using the module (posttest), that was 82.3